High purity nano-crystalline carbon nitride films prepared at ambient temperature by ion beam sputtering - Lu, TR; Kuo, CT; Yang, JR; Chen, LC; Chen, KH; Chen, TM (My University, 1999)
High purity nano-crystalline carbon nitride films have been successfully deposited by ion beam sputtering. A novel biomolecular C-N compound, 6-aminopurine, of which the characteristic features include covalent C-N bonding, high N/C ratio and a six-membered ring structure similar to that in the hypothetical C3N4 crystal, has been employed as the target material. The films can be deposited onto a variety of substrate, such as copper, silver, stainless steel, nickel and silicon wafer at ambient temperature. SAM examination indicates a high nitrogen-to-carbon ratio at about 0.51. XPS, IR and Raman studies reveal that the chemical bonding structures consist mainly of sp(3)-hybridized carbon as well as sp(2)-hybridized nitrogen and carbon. Both TEM and SAM mapping investigations indicate that the film contains a very dense and homogenous distribution of nanocrystalline grains. However, the structures of these crystals are yet to be determined since their TEM diffraction patterns only matched partially with the calculated pattern for beta-C3N4. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: carbon nitride films; ion beam sputtering; nano-crystalline films; bio-molecular targets